Depressive symptoms, perceived control and quality of life among patients undergoing coronary artery bypass graft: a prospective cohort study - Mohannad Eid AbuRuz; Ghadeer Al-Dweik (BMC, 2022)
Abstract Background Coronary artery bypass graft surgery (CABG) is an intervention directed toward improving the Quality of Life (QoL) for patients with coronary artery disease. Depression can affect QoL negatively among this population. Perceived control (PC) decreased the effect of anxiety on QoL, however, this effect has not been well-studies regarding depression. Therefore, the purpose of this study was to check the effect of depression on QoL among CABG patients and to determine if preoperative PC moderates this effect. Methods This was a prospective observational cohort study conducted on a consecutive sample of 200 patients from three hospitals in Amman, Jordan. Depression Anxiety and Stress Scale, Short-Form Health Survey-36, and Arabic version of the Control Attitude Scale-Revised were used to measure depressive symptoms, QoL and PC respectively. Data were analyzed using t test and step wise multiple regression followed by simple slope analysis. Results Postoperative Physical Component Summary (PCS) was better than preoperative PCS (mean ± SD: 38.2 ± 9.4 vs. 36.6 ± 9.5, P < 0.001). Postoperative Mental Component Summary (MCS) was better than preoperative MCS (mean ± SD: 44.3 ± 11.5 vs. 41.4 ± 11.4, P < 0.001). Preoperative depression was higher than postoperative depression; (mean ± SD: 12.8 ± 6.8 vs.11.1 ± 6.7, P < 0.01). Simple slope analysis was significant (simple slope = 0.41, t = 6.1, P < 0.001), indicating the moderating effect of PC. Conclusion Patients undergoing CABG surgery had poor QoL and high levels of depression. Perceived control moderated this relationship and improve QoL. Assessing depression levels and implantation of interventions to enhance perceived control levels prior to operation might improve QoL.